Metal accumulation in fish species of a vast hydrographic network in the Moyen-Ogooué and Haut-Ogooué Provinces of Gabon: Implications for human health - Clency Mikala Okouyi; Michel Mathurin Kamdem; Patricks Voua Otomo; Gaël Darren Maganga (Toxicology Reports)
With an obsolete livestock sector, Gabon relies on its huge hydrographic network rich in fish to supply its populations with animal proteins. This study aimed to conduct metal analyses in four fish species (Oreochromis niloticus, Clarias gariepinus, Chrysichthys nigrodigitatus, Polydactylus quadrifilis) frequently consumed by human populations in the Moyen-Ogooué and Haut-Ogooué Provinces of Gabon and infer the potential human health risks for those populations who rely on these freshwater produces as a source of proteins. Fish were sampled from Ezanga, Oguemoué, Onangué, Nguenè (Moyen-Ogooué) and Grand Poubara (Haut-Ogooué) Lakes during the high flow period (HF) and low flow period (LF) from 2021 to 2022, and analysed for seven heavy metals (HMs) using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) techniques. Throughout the flow periods, and regardless of the lake and fish species, Fe was found to have the highest concentration, followed by Al > Mn > Hg > Pb> As> Cd. The relatively high concentration of Hg was recorded in the muscle tissues of C. gariepinus (6.65 mg. kg−1) sampled during the LF period at Grand Poubara. The concentrations of Hg found in the muscle of all fish species also exceeded the maximum acceptable limits set by the American Environmental Protection Agency. The concentrations of Fe in C. gariepinus (Grand Poubara, LF) and O. niloticus (Onangué, LF), and those of Al in O. niloticus (Nguenè, HF), P. quadrifilis (Onangué, HF) and C. nigrodigitatus (Oguemoué, LF) were amongst the highest concentrations ever reported on the African continent. Health risk assessments indicated a heightened risk of cancer for local populations consuming the fish species from all the lakes investigated. There is a need to implement an increased surveillance programme at national level in order to raise awareness and improve the management of fishery resources while preserving the environment and the health of local populations that rely upon these resources for their subsistence.